Relationship Between Women's Characteristics With Cervic Cancer Incidence - Nabila, Shermy; Dinengsih, Sri; Novelia, Shinta (Universitas Islam Lamongan, 2023)
In Indonesia, every year more than 15,000 cases of cervical cancer are detected, and around 8,000 cases of them die. The incidence of cervical cancer in Indonesia in 2011 reached 100 per 100,000 population per year. To determine the relationship between female characteristics and the incidence of cervical cancer in patients in the gynecology room of the Gatot Soebroto Army Hospital in 2022. This research is a quantitative study with a case control design using primary data with a sample of 58 patients on the 2nd floor of the gynecology room. The sampling technique uses random sampling. Data analysis using univariate and bivariate using chi square. The variables associated with the incidence of cervical cancer were HPV vaccination (p=0.002), early detection of cervical cancer (p=0.003), history of smoking (p=0.009), history of vaginal discharge (p=0.014) and age at first sexual intercourse (p=0.004) with the incidence of cervical cancer, while variables that had no relationship were history of contraception (0.738). There is a relationship between HPV vaccination, early detection of cervical cancer, history of smoking, history of vaginal discharge and age at first sexual intercourse with the incidence of cervical cancer. It is expected to increase women's knowledge about the factors associated with the incidence of cervical cancer.